International trade : theory and policy - Krugman, Paul R (Pearson, 2024)
International Trade: Theory and Policy provides engaging, balanced coverage of the key concepts and practical applications of the discipline. An intuitive introduction to trade theory is followed by detailed coverage of policy applications.